2021
DOI: 10.1002/adma.202004393
|View full text |Cite
|
Sign up to set email alerts
|

2D Copper Tetrahydroxyquinone Conductive Metal–Organic Framework for Selective CO2 Electrocatalysis at Low Overpotentials

Abstract: Metal–organic frameworks (MOFs) are promising materials for electrocatalysis; however, lack of electrical conductivity in the majority of existing MOFs limits their effective utilization in the field. Herein, an excellent catalytic activity of a 2D copper (Cu)‐based conductive MOF, copper tetrahydroxyquinone (CuTHQ), is reported for aqueous CO2 reduction reaction (CO2RR) at low overpotentials. It is revealed that CuTHQ nanoflakes (NFs) with an average lateral size of 140 nm exhibit a negligible overpotential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(122 citation statements)
references
References 64 publications
(84 reference statements)
0
122
0
Order By: Relevance
“…successfully in this field. 101,[122][123][124][125][126][127] Recent advances show that the photocatalytic CO 2 conversion can be carried out in porous polymers even in the absence of metal atoms; 112,128,129 yet this area has not been explored at all with pPIs to date, and presents a significant opportunity to address global challenges presented by continued and growing human activity and influence on the environment. In particular, recent focus has been placed on the direct conversion of CO 2 to useful chemicals (rather than storage).…”
Section: Future Outlookmentioning
confidence: 99%
“…successfully in this field. 101,[122][123][124][125][126][127] Recent advances show that the photocatalytic CO 2 conversion can be carried out in porous polymers even in the absence of metal atoms; 112,128,129 yet this area has not been explored at all with pPIs to date, and presents a significant opportunity to address global challenges presented by continued and growing human activity and influence on the environment. In particular, recent focus has been placed on the direct conversion of CO 2 to useful chemicals (rather than storage).…”
Section: Future Outlookmentioning
confidence: 99%
“…The nanosheets have good electrical conductivity and can effectively promote the electrochemical reduction of CO 2 . Amin and coworkers reported the CO 2 RR electrocatalytic activity study of 2D copper based c‐MOF and copper tetrahydroxyquinone (Cu‐THQ) [49] . c‐MOF is an ideal catalyst material, which can significantly improve the product selectivity and energy efficiency of CO 2 RR, making the 2D Cu‐based conductive MOF, Cu‐THQ has excellent catalytic activity.…”
Section: Catalysismentioning
confidence: 99%
“…Electrochemically generated low valence metal centers like Cu (Cu + ), [ 162 ] Mn 0 , [ 163 ] Co I , [ 164 ] Fe 0 , [ 165 ] Ni I , [ 166 ] Ru 0 , [ 167 ] and Re 0[ 168 ] are general case. For example, Majidi et al.…”
Section: Coordination Compounds In Electrocatalysismentioning
confidence: 99%
“…recently found that there existed reduced Cu (Cu + ) during CO 2 RR for copper tetrahydroxyquinone (Cu‐THQ), which was confirmed by operando Cu K‐edge X‐ray absorption near edge structure (XANES). [ 162 ] Apart from the valance evolution of metal center, the ligand can also be reduced. Wang et al.…”
Section: Coordination Compounds In Electrocatalysismentioning
confidence: 99%